The spirit of Vatican II: the idealist aspects of liturgical architecture in Europe - Katona, Vilmos (Journal of Architecture and Urbanism, 2023)
The purpose of this study is to provide a comprehensive overview of the “idealist” intellectual workshops behind the 20th-century liturgical architecture before and after the Second Vatican Council. These workshops established their concepts on the intriguingly historic presumption that, in order to refresh the Catholic liturgy, one must seek and return to the origins of Christianity. In other words, their worldview was characterized by the spirit of ressourcement, which was one of the great motivators of the new liturgical paradigm brought about by 1962. Ressourcement had both monastic and secular aspects to the invocation – or recreation – of the early apostolic communities by means of new spatial and contextual programs in contemporary church architecture. These programs were conceptually compound, and were often guided or implemented by the clergy itself. The study also sheds light on some of the 21th-century interpretations and the survival of the same ideas in today’s architectural culture.